The Role of Brand Image in Mediating the Influence of Online Customer Reviews and Perceived Ease of Use on Purchase Decisions - Krisna, I Putu; Nita Anggraini, Ni Putu; Dharmadewi Atmaja, Ni Putu Cempaka (AIBPM Publisher, 2024)
The rapid development of technology and information has significantly impacted the online travel and tour business, including Penidago.com. This study aims to determine the effect of online customer reviews and perceived ease of use on purchasing decisions, and the role of brand image in mediating these effects on Penidago.com. A quantitative research design was employed, with a population consisting of all Penidago.com users. A sample of 100 respondents was collected using a questionnaire as the research instrument. The findings reveal that online customer reviews have a positive and significant effect on purchasing decisions, while perceived ease of use has a negative and insignificant effect. Additionally, online customer reviews positively and significantly affect brand image, while perceived ease of use has a positive but insignificant impact. Brand image positively influences purchasing decisions and partially mediates the relationship between online customer reviews and purchasing decisions. However, brand image does not mediate the effect of perceived ease of use on purchasing decisions